Technology Drivers : Engine for Growth : Proceedings of the 6th Nirma University International Conference on Engineering (NUICONE 2017), November 23-25, 2017, Ahmedabad, India /: Engine for Growth : Proceedings of the 6th Nirma University International Conference on Engineering (NUICONE 2017), November 23-25, 2017, Ahmedabad, India. ([2018]) - Unknown
No abstract available